Hormonal and epigenetic regulation of root responses to salinity stress - Ping Yun; Cengiz Kaya; Sergey Shabala (Crop Journal)
Salinity stress is a major environmental stress affecting crop productivity, and its negative impact on global food security is only going to increase, due to current climate trends. Salinity tolerance was present in wild crop relatives but significantly weakened during domestication. Regaining it back requires a good understanding of molecular mechanisms and traits involved in control of plant ionic and ROS homeostasis. This review summarizes our current knowledge on the role of major plant hormones (auxin, cytokinins, abscisic acid, salicylic acid, and jasmonate) in plants adaptation to soil salinity. We firstly discuss the role of hormones in controlling root tropisms, root growth and architecture (primary root elongation, meristematic activity, lateral root development, and root hairs formation). Hormone-mediated control of uptake and sequestration of key inorganic ions (sodium, potassium, and calcium) is then discussed followed by regulation of cell redox balance and ROS signaling in salt-stressed roots. Finally, the role of epigenetic alterations such as DNA methylation and histone modifications in control of plant ion and ROS homeostasis and signaling is discussed. This data may help develop novel strategies for breeding and cultivating salt-tolerant crops and improving agricultural productivity in saline regions.